Placental location and development of preeclampsia: a longitudinal study - Priyadarshini, Ananya; Upreti, Purnima; Nautiyal, Ruchira; Goyal, Mamta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Preeclampsia is one of the leading causes of morbidity and mortality worldwide. A number of pregnant women suffer from it after 20 weeks of their pregnancy. The study was designed to know the association between location of placenta and the development of preeclampsia in pregnant women. the purpose of the study is to determine the incidence of lateral location of placenta and to study the relation between placental location and development of preeclampsia. Methods: A prospective study conducted on pregnant women who attended the antenatal clinic of SRHU Hospital over period of 12 months. The study was hospital based longitudinal study with a sample size of 100 cases presenting over a period of 12 months in Obstetrics and Gynecology Department. Simple Random Sampling was used for random selection of antenatal case at 18 to 24 weeks gestation with singleton pregnancy, after taking written consent and agreeing for follow-up till delivery. Results: Out of the total 100 cases taken for the study, there were 68 cases of lateral placenta and 32 cases of central placenta. Most of the cases belonged to middle class living in urban areas. The development of preeclampsia is mainly due to mineral deficiency and high systolic BP. Conclusions: In present study, 48.5% patients with lateral placenta and 46.9% with central placenta developed pre-eclampsia. There was a significant association that was found between laterality of placenta and development of PIH. The laterally located placenta is associated with increased risk of developing preeclampsia. Therefore, looking for placental laterality at the time of a mandatory antenatal ultrasound scanning (level II) may serve as a non-invasive test to predict pre-eclampsia.